Sugar cookie murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2004)
During the Lake Eden Holiday Buffet, bakery owner Hannah Swensen stumbles upon a recipe for murder when Mrs. Dubinski, a former Vegas showgirl, is found dead with Hannah's mother's antique Christmas cake knife buried in her cleavage.